Enhancing Participation of Children in Schools: A Social Worker's Perspective - Reodique, Karleen May (Asean Social Work Journal, 2025)
Recognizing the importance of children’s participation in ensuring cognitive and social skills development of children, value formation and citizenship, better decision-making for child-centered programs, and strengthening child protection systems, this paper aims to propose a social work model on enhancing children participation in school governance. The model focuses on child-centered intervention approach in addressing the issues and barriers to children’s meaningful participation in decision-making in a public elementary school. Drawing on the assessment conducted in Kalayan Elementary School on the extent and quality of children’s participation, the author proposes a social work model in ensuring the representation of the pupils in the school-based management committee of a public elementary school. The social work model was developed through: (1) needs assessment and further analysis of data using problem tree analysis; (2) developing theory of change to guide the social workers in attaining the desired changes; and (3) creation of a social work model that encapsulates the proposed intervention and expected outcomes.